The role of environmental efficiency and economic development in fertility: implications for public health and sustainability among OECD nations - Mu, Renyan; Zhang, Fuang; He, Shidi; Zhang, Jingshu (Frontiers in Public Health, 2025)
IntroductionAs global economies rapidly develop, the interplay between environmental efficiency, economic development, and public health outcomes has gained significant attention. Air pollution and resource-intensive economic activities threaten both environmental sustainability and human health, including reproductive health and overall well-being.MethodsThis study focuses on OECD member countries, using data from 1999 to 2021. An undesirable outputs-oriented DEA approach is employed to assess environmental efficiency across these countries. Baseline regression analysis is conducted to examine the relationship between environmental efficiency and fertility, while heterogeneity analysis explores the impact of industrial and energy consumption structures. Additionally, the moderating effect of economic development levels is investigated.ResultsThe baseline regression results indicate an inverted U-shaped relationship between environmental efficiency and fertility, where fertility initially declines as environmental efficiency increases, then rises after reaching a certain threshold. Heterogeneity analysis reveals that industrial and energy consumption structures significantly influence this relationship across different regions. Furthermore, economic development is found to be a reverse moderator: in countries with higher economic development levels, the relationship between environmental efficiency and fertility follows a significant U-shaped curve.DiscussionThese findings highlight the necessity of integrating environmental policies with public health strategies. Improvements in environmental efficiency may reduce pollution-related health risks, indirectly supporting fertility recovery in advanced economies. By addressing the interaction between environmental efficiency, economic development, and fertility, this study provides evidence-based insights for designing policies that promote sustainable environmental health and equitable social outcomes.